Pengaruh Lingkungan Belajar, Motivasi Belajar dan Sarana Prasarana terhadap Prestasi Akademik Mahasiswa Program Studi Manajemen Fakultas Ekonomi UNISRI Surakarta - Muhamad Ari Fadjar Sakti; Sunarso; Setyaningsih (Equivalent : Journal of Economic, Accounting and Management, 2025)
Abstract : This research aims to: 1) Find out the significance of the influence of the learning environment on the academic achievement of students in the Management Study Program, Faculty of Economics, Unisri Surakarta. 2) Knowing the significance of the influence of learning motivation on the academic achievement of students in the Management Study Program, Faculty of Economics, Unisri Surakarta. 3) Knowing the significance of the influence of infrastructure on the academic achievement of students in the Management Study Program, Faculty of Economics, Unisri Surakarta. The research was a survey of + 120 students in the Management Study Program, Faculty of Economics, Unisri Surakarta, and 55 students were taken to determine the sample size using the Slovin formula using the lottery technique. The analysis used in this research is multiple linear regression analysis, t test, F test and coefficient of determination. The results of the research and discussion can be concluded: 1) The learning environment has a significant effect on student academic achievement. 2) Learning motivation has a significant effect on student academic achievement. 3) Infrastructure has a significant effect on student academic achievement. The model is accurate in predicting the influence of learning environment variables, learning motivation, and infrastructure on academic achievement. Academic achievement is influenced by learning environment factors, learning motivation, and infrastructure. Meanwhile, other factors that were not included in the research include: learning discipline, emotional intelligence, academic guidance, learning independence, family support, and others. Abstrak :  Penelitian ini bertujuan untuk: 1) Mengetahui signifikansi pengaruh lingkungan belajar terhadap prestasi akademik mahasiswa Program Studi Manajemen Fakultas Ekonomi Unisri Surakarta. 2) Mengetahui signifikansi pengaruh motivasi belajar terhadap prestasi akademik mahasiswa Program Studi Manajemen Fakultas Ekonomi Unisri Surakarta. 3) Mengetahui signifikansi pengaruh sarana prasarana terhadap prestasi akademik mahasiswa Program Studi Manajemen Fakultas Ekonomi Unisri Surakarta. Penelitian bersifat survey pada mahasiswa Program Studi Manajemen Fakultas Ekonomi Unisri Surakarta berjumlah + 120 mahasiswa dan penentuan jumlah sampel menggunakan rumus Slovin diambil sebanyak 55 mahasiswa dengan teknik undian. Analisis yang digunakan dalam penelitian ini adalah analisis regresi linear berganda, uji t, uji F dan koefisien determinasi. Hasil penelitian dan pembahasan dapat disimpulkan: 1) Lingkungan belajar berpengaruh signifikan terhadap prestasi akademik mahasiswa. 2) Motivasi belajar berpengaruh signifikan terhadap prestasi akademik mahasiswa. 3) Sarana prasarana berpengaruh signifikan terhadap prestasi akademik mahasiswa. Model tepat dalam memprediksi pengaruh variabel lingkungan belajar, motivasi belajr, dan sarana prasarana terhadap prestasi akademik. Prestasi akademik dipengaruhi oleh faktor lingkungan belajar, motivasi belajar, dan sarana prasarana. Sedangkan faktor lain yang tidak dimasukkan dalam penelitian diantaranya: disiplin belajar, kecerdasan emosional, bimbingan akademik, kemandirian belajar, dukungan keluarga, dan lain-lain.